2018
DOI: 10.2174/1876325101810010048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Paraquat on Four Rhizobacteria Strains: Pantoea agglomerans, Rhizobium nepotum, Rhizobium radiobacter and Rhizobium tibeticum

Abstract: Background: Soil microorganisms are exposed to herbicides after treatment, which leads to their interaction. The result of this interaction may be the degradation of the herbicides by the microorganisms and by the way, they use the degradation products as an energy source for their own physiological processes, or herbicides have a toxic effect on these microorganisms. Herbicide toxicity becomes severe instantly after application when its concentration in soil is the highest. Paraquat is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…The response of Rhizobium to the two pesticides at 0.01 mg/L concentration, based on the tolerance indices obtained, did not differ significantly from one another (p≤0.05). The findings from the present study are supported by several similar studies which also established that paraquat, dichlorvos and other pesticides negatively influenced the growth of microorganisms in the receiving ecosystems (Nur et al, 2013;Maldani et al, 2018;Mazhari and Ferguson, 2018;Osadebe and George, 2022;Osadebe and Ubochi, 2022). Margino et al (2000), in their study on paraquat in peat land, reported that paraquat concentrations of 20 mg/kg had a strong inhibitory influence on the community dynamics of soil bacteria and fungi.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The response of Rhizobium to the two pesticides at 0.01 mg/L concentration, based on the tolerance indices obtained, did not differ significantly from one another (p≤0.05). The findings from the present study are supported by several similar studies which also established that paraquat, dichlorvos and other pesticides negatively influenced the growth of microorganisms in the receiving ecosystems (Nur et al, 2013;Maldani et al, 2018;Mazhari and Ferguson, 2018;Osadebe and George, 2022;Osadebe and Ubochi, 2022). Margino et al (2000), in their study on paraquat in peat land, reported that paraquat concentrations of 20 mg/kg had a strong inhibitory influence on the community dynamics of soil bacteria and fungi.…”
Section: Resultssupporting
confidence: 89%
“…These xenobiotic compounds are well known to persist in soil and water systems impacting on the physical, chemical, and biological characteristics of these environments. Their fate is any ecosystem is largely contingent on their interaction with the native microbial communities (Maldani et al, 2018;Hamuda, 2020). Studies have shown that about 99.9 % of applied pesticides is lost to the receiving environment where it induces pesticide stress on non-target organisms in that environment due to its accumulation and persistence (Ahemad & Khan, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pantoea is also known to form associations with humans and also a variety of hosts, including plants and insects 10 , 71 73 . Pantonea is also used in industry for bioremediation, herbicides degradation and other toxic products 74 77 . The microbe possesses plant growth-promoting capabilities and is used in agricultural applications 10 , 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Namun, dalam beberapa kondisi herbisida dapat mempercepat terjadinya dekomposisi oleh aktivitas mikroba yang membantu penguraian bahan organik dari gulma yang telah mati sebagai bentuk korelasi posistif dalam bentuk adaptasi terhadap pemberian herbisida ke dalam tanah, sehingga C-organik dapat terjadi peningkatan akan tetapi tidak secara langsung dapat meningkatkan kandungan hara dan bahan organik tanah (Faqihhudin, 2013). bersifat beracun bagi beberapa mikroorganisme, tapi disisi lain juga bermanfaat bagi mikroorganisme lain sebagai sumber karbon, fosfor, atau nitrogen setelah terjadi degradasi (Maldani et al, 2018). Herbisida juga mengurangi proses biokimia yang diatur oleh mikroba tanah dan reaksi enzimatik yang berperan penting dalam menjaga atau meningkatkan kesehatan tanah, termasuk mineralisasi, dan transformasi bio terkait seperti dinamika nutrisi (nitrifikasi, denitrifikasi, dan amonifikasi), reaksi redoks, dan metanogenesis di dalam tanah (Meena et al, 2020).…”
Section: Kandungan C Organik Dan N Total Inceptisolunclassified